New Round-Up 6: Teacher's Book - Evans V. Virginia (Harlow, Longman, 2011)
Lively illustrated exercises to make practice fun and effective Listening tasks Translation practice English in Use sections to practise phrasal verbs, word formation, paraphrasing and idioms Regular Exam ZonesCD-ROM with Exam Zones to provide more grammar and exam practice Teacher's book with answer keys, photocopiable Quizzes and Tests